2021
DOI: 10.1002/rcm.9113
|View full text |Cite
|
Sign up to set email alerts
|

The maximum carbonyl ratio (MCR) as a new index for the structural classification of secondary organic aerosol components

Abstract: Rationale: Organic aerosols (OA) account for a large fraction of atmospheric fine particulate matter and thus are affecting climate and public health. Elucidation of the chemical composition of OA is the key for addressing the role of ambient fine particles at the atmosphere-biosphere interface and mass spectrometry is the main method to achieve this goal.Methods: High-resolution mass spectrometry (HRMS) is on its way to becoming one of the most prominent analytical techniques, also for the analysis of atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 81 publications
2
55
0
Order By: Relevance
“…The regions marked in (a) and (b) were obtained from Zhang et al. (2021) to describe oxidation state of CHON compounds. It should be noted that this comparison can be biased by the extraction method and instruments used for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regions marked in (a) and (b) were obtained from Zhang et al. (2021) to describe oxidation state of CHON compounds. It should be noted that this comparison can be biased by the extraction method and instruments used for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the chemical characteristics of CHON compounds detected in this study with the chemical characteristics of source and ambient aerosol samples reported in previous studies, a modified van Krevelen diagram based on the maximum carbonyl ratio was constructed (Figure 3 and Tables S7 and S8 in Supporting Information ; Zhang et al., 2021). The diagram was divided into five areas, which describe the oxidation states of very highly oxidized organic compounds, highly oxidized organic compounds, intermediately oxidized organic compounds, oxidized unsaturated organic compounds, and highly unsaturated organic compounds (Zhang et al., 2021). The CHON+ and CHON– compounds were located in areas that corresponded to oxidized unsaturated compounds and intermediately oxidized organic compounds, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of compounds in Cluster D (Figure D) are CHOn compounds, present in the region of 1.1 < H/C < 2 and 0.2 < O/C < 0.9. Previous studies suggest that in this region oxidation products of biogenic emissions appear. ,, We confirm this cluster as partly biogenic as we detect the compounds MBTCA (C 8 H 12 O 6 ) and pinic acid (C 9 H 14 O 4 ), which are widely used as oxidation tracers of α-pinene (Figure S9D,E). However, we cannot exclude the contribution of anthropogenic compounds in this cluster.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The maximum carbonyl ratio (MCR) was used to estimate the contribution of carbonyl equivalent groups in the molecule with oxygen number greater than or equal to DBE (Zhang et al, 2021). The value of MCR is calculated as Eq.…”
Section: Molecular Formula Assignmentmentioning
confidence: 99%
“…The maximum carbonyl ratio (MCR) index is suggested as a tool for a better characterization of the sources and the processing of atmospheric OA components (Zhang et al, 2021). Figure 3 As shown in Figure 4, the identified HOMs mainly exist as dimers with m/z of 350∼450 Da.…”
Section: Effects Of Ozone Concentration On Size Distribution and Oxid...mentioning
confidence: 99%